FAKTOR-FAKTOR PENYEBAB KONFLIK SOSIAL ANTAR SISWA KELAS IX SMP NEGERI 3 SUNGAI RAYA - Dwi Kunniarti; Gusti Budjang; Imran Imran (Universitas Tanjungpura, 2017)
AbstractThe problems in this research are the casual factors of social conflict among grade IX students in SMPN 3 Sungai Raya. The research method is descriptive qualitative form. The research used documentation technique with data collection tool in the form of interview guideline. The interview result concluded that communication is the factor of social conflict among students grade IX in SMPN 3 Sungai Raya. Students tend to be wrong in communicating and interacting. The class structure is a casual factor of social conflict among students’ grade IX students in SMPN 3 Sungai Raya. The factor of structure in the classroom are still part of the factors causing conflict among students in the classroom, judging by the attitude of students who prefer to get along with who can help in school affairs. Personality factors causing social conflicts among students grade IX in SMPN 3 Sungai Raya. Different personality with others, who have a quiet personality difficult in socializing, other than that there is a personality who likes to seek attention in school because of lack of attention from family and school.Keywords: Social Conflict, Junior High School Students